Kombinasi Preventive Dan Reactive Maintenance Dengan Simulasi Sistem Dinamik - Subiantoro, Sigit (Program Studi Teknik Mesin, Universitas Trisakti, 2007)
Combination of Prepentive and Reactive Maintenance Using Dynamic SystemSimulation. Maintenance system holds an important role in a company establishment. Less optimal ofmaintenance system will cause disturbance to the production process. To overcome this problem, aquantitative approach model contains of complexion factors was proposed as a solution. Base on thismodel, simulation ofsolution is made by using dynamic system principle and Powersim software. Fromthree scenario wich have been proposed, the scenario third is most optimal, that is suppressingmaintenance costfraction to 5 %value, increasing thepreventive maintenance (PM- 10)fraction valueand decreasing valuefraction ofreactivemaintenance (RM- 0.8).